Hyperammonemia syndrome due to Ureaplasma urealyticum in a kidney transplant recipient: A case of disseminated disease from a fluoroquinolone‐resistant isolate. Issue 5 (2nd June 2020) - Higgins, Andrea B.; Farmakiotis, Dimitrios; Rogers, Ralph; Osband, Adena J.; Seo, Angie; Chen, Brendan; Birkenbach, Mark P.; Crabb, Donna; Xiao, Li; Leal, Sixto; Waites, Ken; Gohh, Reginald; et al.
Abstract: Ureaplasma species (spp.) are common colonizers of the urogenital tract but may cause systemic infection in immunocompromised patients. They release significant amounts of ammonia via urea hydrolysis and have been recently implicated in the pathogenesis of hyperammonemia syndrome after organ transplantation. We describe a unique case of hyperammonemia syndrome after kidney transplant caused by U urealyticum infection, and the first, to our knowledge, case of a fluoroquinolone‐resistant Ureaplasma strain causing hyperammonemia syndrome. A 17‐year‐old female developed intermittent fevers, rising creatinine, sterile pyuria and debilitating polyarthritis approximately 1 year after kidney transplant. Serum ammonia level was elevated, and urine PCR was positive for U urealyticum . Near the end of treatment with levofloxacin, she had rebound hyperammonemia, which preceded clinical relapse of polyarthritis and encephalopathy. Blood and urine PCR and synovial fluid culture were positive for U urealyticum . Susceptibility testing showed fluoroquinolone resistance, but she responded well to azithromycin and doxycycline. The frequency of Ureaplasma spp. infection in immunocompromised patients is probably underestimated due to diagnostic challenges. Ammonia levels were helpful biomarkers of response to antimicrobial therapy in our case. Susceptibility testing of clinical isolates should be pursued. In serious Ureaplasma spp. infections, particularly in immunocompromised patients, two empiric antibiotics may be indicated given the potential for antimicrobial resistance.